Perbandingan Model Deep Learning untuk Klasifikasi Sentiment Analysis dengan Teknik Natural Languange Processing - Firman Pradana Rachman; Handri Santoso (Universitas Merdeka Malang, 2021)
Everyone has an opinion or opinion on a product, public figure, or government policy that is spread on social media. Opinion data processing is called sentiment analysis. In processing large opinion data, it is not enough to only use machine learning, but you can also use deep learning combined with NLP (Natural Language Processing) techniques. This study compares several deep learning models such as CNN (Convolutional Neural Network), RNN (Recurrent Neural Networks), LSTM (Long Short-Term Memory), and several variants to process sentiment analysis data from Amazon and Yelp product reviews.